Understanding fintech excellence: A scholarly review of the diploma fintech model for effective global implementation - Haripin, Haripin; Indraprakoso, Dondy; Wibisono, Gunawan; Utomo, Hargo (International Journal of Financial, Accounting, and Management, 2025)
Purpose: This study examines the global Fintech phenomenon by reviewing research from several countries. It aims to identify best practices, involved journals, applied methods, and knowledge gaps that require further investigation. Methodology/Approach: A systematic literature review was conducted using journals from multiple international databases that discuss fintech practices worldwide. The analysis follows the DIPLOMA Model by Boratynska to systematically evaluate and synthesize the selected studies. Results/Findings: Based on the DIPLOMA Fintech Model, Indonesia emerges as the leading country in implementing fintech practices, fulfilling all five dimensions of the model. This achievement positions Indonesia as a potential benchmark for other countries aiming to strengthen their fintech ecosystems. Malaysia, China, and Brazil follow by meeting four dimensions, indicating strong development. The United Kingdom, Germany, Argentina, and South Africa fulfill three dimensions, reflecting moderate fintech maturity. Meanwhile, Sub-Saharan countries and Nigeria meet only one dimension, highlighting significant gaps in fintech readiness and infrastructure. Conclusion: Indonesia fulfills all five DIPLOMA dimensions, confirming its position as a global leader in fintech implementation and innovation. This illustrates Indonesia’s potential to serve as a reference for other countries. Limitations: This study is limited by the selection of countries from only four continents, excluding Australia. The use of a relatively small number of articles also indicates the need for broader literature coverage. Contribution: The study shows that fintech success is not solely determined by development level, but by a combination of supportive factors that enable even developing countries to excel.